PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL QUANTUM TEACHING DI SEKOLAH DASAR - riadi, egi rahmad; hamimah, hamimah; amerta, sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The researchisanimed to improve the students learning outcomes by using Quantum Teaching Model in learning the Social Study Subject at4th grade of SD 10 Bandar Buat. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research wereteachers and 30 students. The result of research was improve a) lesson plan the cycles of I was 78,5% and the cycles II of 89,3% b) implementation theacher’s activity of I cycles was 76,6% and II cycles was 87,5% while implementation student activity of I cycles was 76,6% and II cycles was 87,5% c) the student learning outcomes in the I cycles was 75,3% and II cycles was 85%. It can be concluded that used Quantum Teaching Model can improve students achievement in learning social study of elementary school. With persentase increase 13%.Keyword : Learning outcomes, Social Study, Quantum Teaching